Revenge of the Living Dummy : Goosebumps HorrorLand #1 - Stine, R. L., 1943- (New York : Scholastic, 2008)
Britney battles against her cousin's new ventriloquist dummy and discovers a frightening secret in a new amusement park called HorrorLand.
Keywords: Amusement parks -- Fiction; Puppets -- Fiction; Horror stories